MODERATING EFFECT OF RISK MANAGEMENT COMMITTEE ON BOARD ATTRIBUTES AND FIRM SURVIVAL AMONG LISTED MANUFACTURING COMPANIES IN NIGERIA - Yusuf Labija Amana; Ibrahim Magaji Barde; Aliyu Suleiman Kantudu (Malete Journal of Accounting and Finance)
The ability of a firm to endure, adapt and prosper over time is a multifaceted outcome influenced by an interplay of internal and external factors. However, the precise mechanisms and specific dynamics that contribute to sustained firm survival remain unclear. This study investigated the moderating effect of risk management committee on the relationship between board attributes and firm survival among listed manufacturing companies in Nigeria. The study utilized secondary data obtained from a sample of 34 manufacturing companies listed on the Nigerian Exchange Group during the period from 2011-2022. The data were analysed using Generalized Least Square. Findings indicate that board independence, board size and board expertise were statistically associated with firm survival, while board gender diversity has an insignificant impact on firm survival. The risk management committee on the other hand was found to exert no significant moderating influence on the relationship between board attributes and firm survival. The study concluded that board attributes are vital governance mechanisms capable of enhancing firm survival. It therefore recommended that shareholders of listed manufacturing companies in Nigeria should focus on optimal board size and should prioritize directors with requisite expertise rather than independence.